Effect of text messaging plus peer navigation on viral suppression among youth with HIV in the icare Nigeria pilot study (2021)
Background: Consistent with the global trend, youth with HIV (YWH) in Nigeria have high rates of viral nonsuppression. Hence, novel interventions are needed. Setting: Infectious Diseases Institute, College of Medicine, University of Ibadan, Nigeria. Methods: In a single-arm trial, participants aged 15–24 years received 48 weeks of a combination intervention, comprising daily 2-way text message medication reminders plus peer navigation. The primary outcome measure was viral suppression less than 200 copies/mL. The secondary outcome measures included self-reported adherence on avisual analog scale and medication possession ratio, each dichotomized as $90% (good) or ,90% (poor) adherence. The outcomes were analyzed using McNemar test. Retention in care, intervention feasibility and acceptability, and participants’ satisfaction were also assessed. Results: Forty YWH (50% male participants) were enrolled: meanage 19.9 years (SD = 2.5), 55% perinatally infected, and 35% virologically suppressed at baseline. Compared with baseline, the odds of virologic suppression was higher at 24 weeks (odds ratio = 14.00, P , 0.001) and 48 weeks (odds ratio = 6.00, P = 0.013). Self-reported adherence ($90%) increased from baseline at 24 weeks (63%, P = 0.008) and 48 weeks (68%, P = 0.031). Medication possession ratio $90% increased at weeks 24 and 48 (85% and 80%, respectively), achieving statistical significance at 24weeks alone (P = 0.022). Retention in care at 48 weeks was 87.5%. All (37/37) participants at week 48 were fully or mostly satisfied with the intervention. Conclusion: Daily 2-way text message reminders plus peer navigation is a promising combination intervention to improve viral suppression among YWH in Nigeria.